2023
DOI: 10.1088/1402-4896/accfc5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structural, optoelectronic, elastic, and thermoelectric properties of cubic ternary fluoro-perovskites sodium based NaMF3 (M = Si and Ge) compounds for heterojunction solar cells applications

Abstract: In current research the structural, optoelectronic, elastic, and thermoelectric properties of NaMF3 (M = Si and Ge) ternary perovskites (Halide Perovskites) compounds using first-principle modeling are computed within the DFT framework. The obtained results of phonons dispersion curves and the tolerance factor is calculated for NaSiF3 and NaGeF3 and is found to be 1.001 and 1.004 respectively, which reveals that these compounds are structurally and thermodynamically stable in cubic phase. The elastic constant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…We also confirmed that the HSE06 hybrid functional yielded remarkably larger band gaps compared to the PBE functional for the fluoride perovskites due to a upward shift of conduction bands and a downward shift of valence bands. Experimental and theoretical data are not yet available for these fluoride perovskites, except KGeF 3 (NaSiF 3 ), for which the band gap was calculated to be 2.00 (1.15) eV with the PBE (HSE06) functional 41,67 in accordance with our calculation of 1.97 (1.24) eV with the same XC functional (see Table 1). As far as believing the HSE06 calculations, the Si-based fluoride perovskites ASiF 3 (A = Na, K) were found to be suitable for visible light absorber applications because of their appropriate band gaps of 1.24 eV (A = Na) and 1.37 eV (A = K).…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…We also confirmed that the HSE06 hybrid functional yielded remarkably larger band gaps compared to the PBE functional for the fluoride perovskites due to a upward shift of conduction bands and a downward shift of valence bands. Experimental and theoretical data are not yet available for these fluoride perovskites, except KGeF 3 (NaSiF 3 ), for which the band gap was calculated to be 2.00 (1.15) eV with the PBE (HSE06) functional 41,67 in accordance with our calculation of 1.97 (1.24) eV with the same XC functional (see Table 1). As far as believing the HSE06 calculations, the Si-based fluoride perovskites ASiF 3 (A = Na, K) were found to be suitable for visible light absorber applications because of their appropriate band gaps of 1.24 eV (A = Na) and 1.37 eV (A = K).…”
Section: Resultssupporting
confidence: 77%
“…41 bThe band gap were calculated with HSE06 functional. 67 cOur previous first-principles work using Quantum ESPRESSO code. 68 dOur previous first-principles work using VASP code.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Among the properties exhibited by perovskite materials are thermoelectricity, dielectricity, superconductivity, ferroelectricity, optical properties, and various other distinctive characteristics. 8–10 A particular class of perovskites, recognized as chloroperovskites or metal halide perovskites, involve the replacement of the X-anion with a halogen element, commonly chlorine (Cl). Chloroperovskites, which are widely found in perovskite structures, are represented by the formula ABCl 3 , where “A” and “B” can represent alkali metals, alkaline earth metals, transition metals, and “Cl” represents chlorine.…”
Section: Introductionmentioning
confidence: 99%
“…The structural, thermoelectric, half-metallic, optical, and thermoelectric properties of different classes of perovskites such as A 2 BCl 6 (A = Cs, K and B = Se, Sn, Ta, Te, Ti, W, Zr, Mn, Mo, Os, Pd, Pt, Re, Ru, Tc, W), 14 Cs 2 ABF 6 (AB = BiAu, AgIr, CuBi, GaAu, InAs, InAg, InAu, InSb and InBi), 15 Sr 2 EuReO 6, 16 Ba 3 B(Nb,Ta) 2 O 9 (B = Mg, Ca, Sr, Cd, Hg, Zn, Fe, Mn, Ni, and Co), 17 XZrO 3 (X = Ca, Sr, Ba), 18 SrMO 3 (M = Hf and Pt), 19 AgBeX 3 (X = F and Cl), 20 AGeF 3 (A = Ga and In), 21 LiRCl 3 (R = Be and Mg), 22 NaMF 3 (M = Si and Ge), 23 AlRF 3 (R = N, P), 24 and BWF 3 (W = S and Si) 25 were recently investigated by different researchers using DFT methods. These compounds were suggested to be good candidates for using in thermoelectric, spintronic, optical, energy storage, and optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%